2016
DOI: 10.3390/molecules21081050
|View full text |Cite
|
Sign up to set email alerts
|

Achillea schurii Flowers: Chemical, Antioxidant, and Antimicrobial Investigations

Abstract: This study aims to evaluate the phenolic profile, and antioxidant and antimicrobial activity of Achillea schurii Sch.-Bip., an endemic species from Romania that has not been investigated yet. The chromatographic profile of the phenolic components was obtained using the HPLC-MS method, while the total polyphenol, flavonoid, caffeic acid derivative contents were quantified using spectrophotometric methods. The antioxidant activity was evaluated using different methods: DPPH radical scavenging, hemoglobin ascorba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 34 publications
2
51
0
Order By: Relevance
“…Compound 2 presented a UV spectrum and product ions similar to p-coumaric acid. The presence of p-coumaric acid was previously reported in this species by different authors, 8,11,13,14 although that identity was discarded in our case, since the compound detected herein eluted earlier than a standard of p-coumaric acid. Therefore, peak 2 was just tentatively assigned as a p-coumaric acid derivative.…”
Section: Phenolic Compoundsmentioning
confidence: 58%
See 2 more Smart Citations
“…Compound 2 presented a UV spectrum and product ions similar to p-coumaric acid. The presence of p-coumaric acid was previously reported in this species by different authors, 8,11,13,14 although that identity was discarded in our case, since the compound detected herein eluted earlier than a standard of p-coumaric acid. Therefore, peak 2 was just tentatively assigned as a p-coumaric acid derivative.…”
Section: Phenolic Compoundsmentioning
confidence: 58%
“…u; loss of a deoxyhexosyl-hexoside residue), which allowed its assignment as chrysoeriol-7-O-rutinoside, taking into account its previous identification in another Mentha species, such as Mentha × villosa. 21 The presence of luteolin-7-O-glucoside and luteolin has been reported in M. spicata, 7,8,13,14,22 although, to the best of our knowledge, the two compounds detected herein have not been reported in M. spicata. The M. spicata reserve lot presented a higher concentration of all the identified compounds than the standard lot, and both types of samples presented rosmarinic acid as the most abundant phenolic compound.…”
Section: Phenolic Compoundsmentioning
confidence: 67%
See 1 more Smart Citation
“…kotschyi , A. lycaonica , respectively, 96.93 mg GAE/g DW in A. schurii , 22.76–113.34 mg GAE/g DW in A. biebersteinii , 23.62–41.13 mg GAE/g DW in A. phyrgia in many studies. On the other hand, TFC values were reported in previous researches between 4.12 and 79.163 mg QE/g DW . It has been seen that there is no research about A. gypsicola at the literature reviews among Achillea species in terms of TFC.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that some Achillea species had the phenolic and flavonoid compounds in previous many studies. The major polyphenols of species belonging to Achillea genus were determined as rutin and isoquercitrin in A. schurii , 7‐ O ‐ β ‐glucosyl apigenin in A. moschata , sinapic acid and chlorogenic acid in A. phyrgia , gallic acid and rutin in A. aucheri , caffeic acid and 1,3‐dicaffeoylquinic acid in A. millefolium , chlorogenic acid and apigenin in A. filipendulina , p ‐coumaric acid, ferulic acid, luteolin‐7‐ O ‐glycoside, luteolin and quercetin in A. pachycephala by the researchers.…”
Section: Resultsmentioning
confidence: 99%